27.7k views
3 votes
If f(x) = - x, find f -1(x).f -1(x) = x f -1(x) = -xf -1(x) = √xf -1(x) = 3√x

If f(x) = - x, find f -1(x).f -1(x) = x f -1(x) = -xf -1(x) = √xf -1(x) = 3√x-example-1
User Anhlc
by
5.6k points

1 Answer

4 votes

Given:


f(x)=-x

Required:


We\text{ need to find }f^(-1)(x).

Step-by-step explanation:


\text{ Let f\lparen x\rparen=y and }x=f^(-1)(y).
Substitute\text{ f\lparen x\rparen=y and }x=f^(-1)(y)\text{ in the equation f\lparen x\rparen=-x.}
y=-f^(-1)(y).

Multiply both sides of the equation by (-1).


(-1)y=-(-1)f^(-1)(y).
-y=f^(-1)(y).
f^(-1)(y)=-y

Replace y=x in the equation.


f^(-1)(x)=-x

Final answer:


f^(-1)(x)=-x

User Fedab
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.